2016
DOI: 10.25130/tjes.23.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance Characteristics of LPG and Gasoline - Fuelled Single Cylinder SI Engine

Abstract: The investigations have been concentrated on decreasing fuel consumption by using alternative fuels and on lowering the concentration of toxic components in combustion products. LPG as an alternative to gasoline has emerged as a solution to the deteriorating urban air quality problem, especially in an oil country like Iraq. LPG has already been used as cooking fuel in Iraq. In the present paper practical tests of various operating parameters and concerns have been prepared for better understanding of operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The experimental study determined that selecting the right material of manufacture for burner is important for moderating air pollutants from combustion of LPG and enhance air quality greatly. They found that the burners made of cast iron and brass have emission indices which satisfactory standard limit by International Organization for Standardization and other regulations [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study determined that selecting the right material of manufacture for burner is important for moderating air pollutants from combustion of LPG and enhance air quality greatly. They found that the burners made of cast iron and brass have emission indices which satisfactory standard limit by International Organization for Standardization and other regulations [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…But the process of erosion occurs due to chemical or physical forces [22][23][24][25][26][27]; for example, the erosion of rocks occurs due to rainwater falling on them. In short, the erosion process may occur as part of the erosion process but the erosion process cannot occur as a result of the erosion [28][29][30][31][32] as appearance in Figure 1.…”
Section: Introductionmentioning
confidence: 99%